MiR-29a Increase in Aging May Function as a Compensatory Mechanism Against Cardiac Fibrosis Through SERPINH1 Downregulation - Rusu-Nastase, Evelyn Gabriela; Lupan, Ana-Mihaela; Marinescu, Catalina Iolanda; Neculachi, Carmen Alexandra; Preda, Mihai Bogdan; Burlacu, Alexandrina (Frontiers in Cardiovascular Medicine, 2022)
Deregulation of miRNA profile has been reportedly linked to aging process, which is a dominant risk factor for many pathologies. Among the miRNAs with documented roles in aging -related cardiac diseases, miR-18a, -21a, -22, and -29a were mainly associated with hypertrophy and/or fibrosis; however, their relationship to aging was not fully addressed before. The purpose of this paper was to evaluate the variations in the expression levels of these miRNAs in the aging process. To this aim, multiple organs were harvested from young (2-3-mo-old), old (16-18-mo-old) and very old (24-25-mo-old) mice and the abundance of the miRNAs was evaluated by quantitative RT-PCR. Our studies demonstrated that miR-21a, miR-22 and miR-29a were up-regulated in the aged heart. Among them, miR-29a was highly expressed in many other organs, i.e., brain, skeletal muscle, pancreas and kidney, and its expression was further upregulated during the natural aging process. Western blot, immunofluorescence, and xCELLigence analyses concurrently indicated that overexpression of miR-29a in muscle cells decreased the collagen levels as well as cell migration and proliferation. Computational prediction analysis and overexpression studies identified SERPINH1, a specific chaperone of procollagens, as a potential miR-29a target. Corroborating to this, significantly downregulated SERPINH1 levels were found in skeletal muscle, heart, brain, kidney and pancreas harvested from very old animals, therefore indicating a role of the miR-29a-SERPINH1 axis in the aging process. In vitro analysis of miR-29a effects on fibroblast and cardiac muscle cells pointed towards a protective role of miR-29a on aging-related fibrosis, by reducing cell migration and proliferation. In conclusion, our study indicates an adaptive increase of miR-29 in natural aging process and suggests its role as a transcriptional repressor of SERPINH1, with potential therapeutic value against adverse matrix remodeling and aging-associated tissue fibrosis.